1993
DOI: 10.1111/j.1476-5381.1993.tb13935.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of somatostatin receptors in guinea‐pig isolated ileum, vas deferens and right atrium

Abstract: 1 Somatostatin14 (SS14) inhibits neurogenically mediated contractile responses in guinea-pig ileum and vas deferens and exerts a direct negative inotropic action in guinea-pig spontaneously beating right atrium. In this study, the receptors mediating these inhibitory effects have been characterized by comparing the potencies of several cyclic somatostatin analogues. 2 In the guinea-pig ileum, SS14, somatostatin28 (SS28), somatostatin25 (SS25) and several smaller cyclic somatostatin analogues including octreoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Another correlate to sst2 binding is inhibition of tumor growth where again the short cyclic analogues of somatostatin are extremely potent agonists (see Buscail et al 1993). Finally, it has recently be suggested that sst2 receptors may be involved in mediating the inhibition of neurogenically mediated contraction in the guinea-pig ileum (Feniuk et al 1993) and contraction in the rat distal colon (McKeen et al 1994). However, the similar pharmacological characteristics of sst2 and ssts receptors do not allow to decide conclusively whether functional effects produced by short synthetic analogues of SRIF are mediated by one or the other of these two receptors.…”
Section: Discussionmentioning
confidence: 91%
“…Another correlate to sst2 binding is inhibition of tumor growth where again the short cyclic analogues of somatostatin are extremely potent agonists (see Buscail et al 1993). Finally, it has recently be suggested that sst2 receptors may be involved in mediating the inhibition of neurogenically mediated contraction in the guinea-pig ileum (Feniuk et al 1993) and contraction in the rat distal colon (McKeen et al 1994). However, the similar pharmacological characteristics of sst2 and ssts receptors do not allow to decide conclusively whether functional effects produced by short synthetic analogues of SRIF are mediated by one or the other of these two receptors.…”
Section: Discussionmentioning
confidence: 91%
“…A similar neuronal interaction is suggested to regulate tachykinin release from longitudinal muscle motoneurones (22). Thus somatostatin is likely to act within the enteric circuits controling peristalsis rather than at the level of the neuromuscular junction, and this would explain the ability of SRIF to attenuate neurogenically mediated contraction of the guinea pig ileum (14,18,24,36,45).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exogenous SRIF on intestinal motility are complex. In the guinea pig ileum, both excitatory and inhibitory effects, operating through prejunctional mechanisms (14,18,24,36,45), have been described. The contractile response of the rat colon to SRIF also appears to involve activation of noncholinergic nerves (33), possibly by a process of disinhibition of vasoactive intestinal peptide (VIP) ergic/nitrergic interneurones supplying longitudinal muscle motoneurones (22).…”
mentioning
confidence: 99%
“…Following a 60 min interval a second cumulative curve to the test agonist was obtained as described above. Using such a protocol, it has previously been shown that concentration-effect curves to SRIF are highly reproducible Feniuk et al, 1993).…”
Section: Guinea-pig Vas Deferensmentioning
confidence: 99%